2017
DOI: 10.1093/ntr/ntx138
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Delivery to the Aerosol of a Heat-Not-Burn Tobacco Product: Comparison With a Tobacco Cigarette and E-Cigarettes

Abstract: Nicotine delivery to the smoker is expected to play an important role in the ability of any harm-reduction product to successfully substitute smoking. This study evaluated the content and nicotine delivery to the aerosol of a heat-not-burn tobacco product (IQOS) in comparison with e-cigarettes and a tobacco cigarette. The main findings were that the heat-not-burn tobacco sticks contained similar nicotine concentration to tobacco cigarettes, and that the levels of nicotine delivered to the aerosol of the heat-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 32 publications
3
109
1
3
Order By: Relevance
“…Considering the past experience of tobacco industry science , it is reasonable to be cautious and emphasize the importance to have independent studies replicating research published by the industry. Until now, this and other independent studies have, for the most part, verified the manufacturer reports .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Considering the past experience of tobacco industry science , it is reasonable to be cautious and emphasize the importance to have independent studies replicating research published by the industry. Until now, this and other independent studies have, for the most part, verified the manufacturer reports .…”
Section: Discussionsupporting
confidence: 63%
“…It is expected that smokers would want to obtain a similar amount of nicotine from these products as from smoking tobacco cigarettes. Three studies have shown that IQOS delivers approximately 30% lower levels of nicotine to the aerosol compared to a commercial or standardized tobacco cigarette . Therefore, it is possible that smokers who switch to IQOS might use more intense puffing patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The smoke that is released from heating has the same harmful constituents of conventional tobacco cigarette smoke. Preliminary research indicates that HNB tobacco products provide more nicotine than e-cigarettes but less than traditional cigarettes [110]. More research on these devices is needed.…”
Section: Approaches To Tobacco Harm Reductionmentioning
confidence: 99%